KARAKTERISTIK DAN PENANGANAN PENDERITA SINDROM RUBELA KONGENITAL DI PUSAT MATA NASIONAL RUMAH SAKIT MATA CICENDO (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2021)
Introduction : Congenital rubella syndrome is a collection of symptoms caused by rubella virus infection during pregnancy. Congenital rubella syndrome often associated with ocular and systemic disease that are important for early diagnosis and management to prevent visual deprivation. Purpose : To determine the characteristic, clinical manifestation and management associated with congenital rubella syndrome in Cicendo Eye Hospital National Eye Center during January 2017 ? December 2020. Methods :This was retrospective observational study and conducted from January 2017 ? December 2020. The medical records of patients diagnosed with laboratory confirmed congenital rubella syndrome were included. We studied the demographic profile, associated ocular and systemic manifestation, and the management. Results : The study included 137 eyes of 84 patients with congenital rubella syndrome. Median duration of postoperative follow up was 9 months. Most patients were below 6 months of age and most patients were presented with bilateral manifestation. Ocular manifestations were congenital cataract, congenital glaucoma and pigmentary retinopathy. Non ocular manifestations were congenital heart disease, hearing impairment, microcephaly and developmental delay. Irrigation aspiration with primary posterior capsulotomy and anterior vitrectomy without intraocular lens implantation was the most frequent technique. Visual axisopacity was complication that were found after surgery. Conclusions :There were various ocular and systemic manifestation of congenital rubella syndrome. Surgical management were performed in all cases with irrigation aspiration with primary posterior capsulotomy and anterior vitrectomy was the most frequent technique. Keywords : Congenital rubella syndrome, ocular and non ocular manifestation, cataract and glaucoma surgery